2018
DOI: 10.31165/nk.2018.112.534
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Online Activism: Breastfeeding Activism (Lactivism) on Facebook

Abstract: Online support communities for people with various health problems and related online activist groups have been the focus of scholarly attention for three decades. The arrival of social media increased the popularity and breadth of both phenomena. Breastfeeding online activism represents an interesting case in how it connects the (health) support and activist online presences of breastfeeding women. Furthermore, breastfeeding activism - or lactivism - is a form of embodied activism, often performed through bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(25 reference statements)
0
3
0
1
Order By: Relevance
“…In particular, women felt that they could not talk about using formula milk or mixed feeding. Online breastfeeding discourse can be polarised, with some using it to express very strong attitudes around the importance of exclusive breastfeeding in a way that is not always helpful (Mecinska, ). Research shows that women often feel pressure to breastfeeding exclusively (Sheehan & Schmied, ), feel shamed or ostracised if they discuss formula milk (Thomson, Ebisch‐Burton, & Flacking, ), or struggle to find information around mixed feeding (Brown, ) despite the majority of women in the United Kingdom using formula at some point (McAndrew et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, women felt that they could not talk about using formula milk or mixed feeding. Online breastfeeding discourse can be polarised, with some using it to express very strong attitudes around the importance of exclusive breastfeeding in a way that is not always helpful (Mecinska, ). Research shows that women often feel pressure to breastfeeding exclusively (Sheehan & Schmied, ), feel shamed or ostracised if they discuss formula milk (Thomson, Ebisch‐Burton, & Flacking, ), or struggle to find information around mixed feeding (Brown, ) despite the majority of women in the United Kingdom using formula at some point (McAndrew et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One study in Australia found that online breastfeeding support groups are a source of information and emotional reassurance (Bridges, Howell, & Schmied, 2018). Queries can often be answered quickly and easily due to the history of the group who have stored simple responses such as images and memes that can answer common questions (Mecinska, 2018). However, it is often the emotional aspect, and "authentic presence" that women value, typically when feeling isolated and alone during night feeds (Bridges et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estas manifestaciones culturales y civiles deben ser consideradas dentro del llamado lactivismo militante (Faircloth, 2013) que demanda más visibilidad, ya sea por medio de intervenciones artísticas (Epp Buller, 2016;Sanz Vidal, 2017), ya desde la mostración de sí en el universo virtual (Boon y Pentney, 2015;Locatelli, 2017;Mecinska, 2018), ya desde políticas de transmisión del conocimiento concretas (Massó Guijarro, 2013a, 2015a, 2015by 2015c o desde manifestaciones masivas espontáneas (Magallanes y Bard Wigdor, 2017).…”
Section: Introductionunclassified